Socioeconomic position is associated with glycemic control in youth and young adults with type 1 diabetes. Issue 8 (21st September 2020) - Sutherland, Melanie W.; Ma, Xiaonan; Reboussin, Beth A.; Mendoza, Jason A.; Bell, Bethany A.; Kahkoska, Anna R.; Sauder, Katherine A.; Lawrence, Jean M.; Pihoker, Catherine; Liese, Angela D.
Abstract: Objective: Health inequities persist in youth and young adults (YYA) with type 1diabetes in achieving optimal glycemic control. The purpose of this study was to assess the contribution of multiple indicators of social need to these inequities. Research design and methods: Two hundred and twenty two YYA withtype 1 diabetes enrolled in the SEARCH Food Insecurity Study in South Carolina and Washington between the years 2013 and 2015 were included. Latent class analysis was used to identify socioeconomic profiles based on household income, parental education, health insurance, household food insecurity, and food assistance. Profiles were evaluated in relation to glycemic control using multivariable linear and logistic regression, with HbA1c > 9%(75 mmol/mol) defined as high‐risk glycemic control. Results: Two profiles were identified: a lower socioeconomic profile included YYA whose parents had lower income and/or education, and were more likely to be uninsured, receive food assistance, and be food insecure. A higher socioeconomic profile included YYA whose circumstances were opposite to those in the lower socioeconomic profile. Those with a lower socioeconomic profile were more likely to have high‐risk glycemic control relative to those with a higher socioeconomic profile (OR = 2.24, 95%CI = 1.16‐4.33). Conclusions: Lower socioeconomic profiles are associated with high‐risk glycemic control among YYA with type 1 diabetes. This supports recommendations that care providers of YYA with type 1 diabetes assess individual social needs in tailoring diabetes management plans to the social context of the patient.